Peran Pemuda Dalam Upaya Pengelolaan Sampah Berbasis Partisipasi Masyarakat Di Desa Kotarindau - Fitriyana S.; Harnida Wahyuni Adda (Jurnal Nusantara Berbakti, 2023)
Efforts to reduce and handle waste require the full participation of the community. Community participation is very important because the community as a waste producer, the community knows best about the condition of waste management in their environment. This research is a descriptive research, namely making systematic, factual, and accurate descriptions of the facts and characteristics of a particular population or area. The data analysis techniques used to achieve the objectives of this study are: the Frequency Distribution analysis method, which processes data using various simple statistical calculations, for example: amounts, differences and percentages of data. The results of this study indicate that the role of youth in community participation-based waste management is very important in Kotarindau Village.